Defining maritime piracy: the problem with the law: research - Otto, Lisa (Acta criminologica, 2018)
Maritime piracy is clearly defined under international law, briefly, as any act of violence committed for private ends on the high seas by one vessel against another. However, this definition is based on common law that arose during piracy’s Golden Age, more than 300 years ago, and as such does not reflect the modern realities of practical activity. This raises several challenges around understanding and fighting back against piracy. Indeed, the inadequacy of the legal definition can be seen in application with current ‘piracy’ hotspots in West Africa and Southeast Asia, where, despite acts occurring being branded and dealt with as piracy, do not actually technically constitute piracy, because they take place in territorial waters, and are sometimes motivated by political ends rather than private gain. Given these limitations and the implications of the differing ideas surrounding how piracy should be defined, it is greatly important that a more applicable definition for piracy and the subset of crimes referred to as piracy be developed.